2016
DOI: 10.1021/acs.jpcc.6b04721
|View full text |Cite
|
Sign up to set email alerts
|

Nature of Electromagnetic-Transparent SiO2 Shell in Hybrid Nanostructure Enhancing Electromagnetic Attenuation

Abstract: The understanding of the structure−activity relationship can help us design desired functional materials. SiO 2 shell is widely used as a physicochemical inert layer to protect materials from corrosion or oxidization. But, in electromagnetic (EM) absorption studies, silica shell, supposed to be EM transparent, has been found to significantly influence the EM absorption performance. Here, we studied the microstructure, EM parameters, and electronic structure of silica shell coated SiC/Co (SiC/Co@SiO 2 ) nanowir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(14 citation statements)
references
References 44 publications
(56 reference statements)
0
14
0
Order By: Relevance
“…As a result, the carbon coated Co-SiC nanocomposites exhibited a high EM absorption performance with a broad absorption bandwidth. Liang 85 synthesized SiC/Co/SiO 2 material of multi-shell structure with a broad absorption bandwidth from 9.1 to 18 GHz (R L < À10 dB). The SiO 2 shell introduced charge transfer between SiO 2 and Co to achieve the impedance matching, resulting in promotion of the incident EM waves entering into the absorber.…”
Section: Modication Of Sic Using Magnetic Materialsmentioning
confidence: 99%
“…As a result, the carbon coated Co-SiC nanocomposites exhibited a high EM absorption performance with a broad absorption bandwidth. Liang 85 synthesized SiC/Co/SiO 2 material of multi-shell structure with a broad absorption bandwidth from 9.1 to 18 GHz (R L < À10 dB). The SiO 2 shell introduced charge transfer between SiO 2 and Co to achieve the impedance matching, resulting in promotion of the incident EM waves entering into the absorber.…”
Section: Modication Of Sic Using Magnetic Materialsmentioning
confidence: 99%
“…However, due to poor dielectric properties aroused by single polarization, the weak MA capacity of SiC‐based materials greatly restricts their practical applications 9,17 . Therefore, a lot of efforts have been done in the past decades on the methods of introducing more multiple polarizations into SiC‐based materials to adjust their dielectric or magnetic properties so as to enhance their MA performance 17‐19 . For instance, Liang et al found that the doping of cobalt into SiC nanowires could enhance the magnetic loss of SiC nanowires, leading to the improvement of their MA performance.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Liang and his colleagues demonstrated that after coating a layer of SiO 2 on SiC/Co nanowires, the MA performance of the as‐obtained products were further improved with an effective absorption bandwidth (RL < −10 dB) extended to 8.9 GHz. This improved MA performance could be attributed to the transfer of charge at the core‐shell interface 19 . Hence, if the element doping and heterostructure construction are combined to modify SiC, it is predictable that the as‐obtained SiC materials will exhibit improved MA properties.…”
Section: Introductionmentioning
confidence: 99%
“…EMI shielding is necessary for lots of electrical–electronic equipment to prevent undesirable interference effects caused by electromagnetic waves. For this reason, EMI shielding performance of a number of popular materials such as carbon shell coated SiC (SiC@C), SiC/Co, graphene, silica shell coated SiC/Co (SiC/Co@SiO 2 ), reduced graphene oxides (r‐GOs), silica coated on carbon fiber (CF/SiO 2 ), and SiC foam has been evaluated in the literature.…”
Section: Introductionmentioning
confidence: 99%